2020
DOI: 10.1021/acs.energyfuels.0c00265
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis Oil from Scrap Tires as a Source of Fuel Components: Manufacturing, Fractionation, and Characterization

Abstract: One of the most efficient among the methods of managing waste tire rubber is the pyrolysis process which allows for obtaining pyrolysis oil. The as-received, raw tire pyrolysis oil (rTPO) is a complex mixture whose components exhibit a wide boiling temperature range, reflected in the physicochemical properties influencing injection, combustion, performance, and emission. The present contribution is aimed at producing TPO via steam-assisted pyrolysis followed by its fractionation by vacuum distillation. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Reports on the fractionation of TPO and acquisition of the mentioned chemicals (BTEX, limonene) are rather scarce in the literature. Most of the studies on distillation are found using lab-scale facilities operated at batch mode and aimed at producing fuel-like streams. ,, In addition, BTEX and limonene production are mainly focused via catalytic pyrolysis. To the best of the authors’ knowledge, this is the first study showing the continuous fractioning of TPO in a pilot-scale distillation plant using a packed column. The goal of this work is not only to demonstrate the technical feasibility to recover valuable products from TPO by distillation but also to gather key information for future optimization steps, as well as for bringing the process at industrial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Reports on the fractionation of TPO and acquisition of the mentioned chemicals (BTEX, limonene) are rather scarce in the literature. Most of the studies on distillation are found using lab-scale facilities operated at batch mode and aimed at producing fuel-like streams. ,, In addition, BTEX and limonene production are mainly focused via catalytic pyrolysis. To the best of the authors’ knowledge, this is the first study showing the continuous fractioning of TPO in a pilot-scale distillation plant using a packed column. The goal of this work is not only to demonstrate the technical feasibility to recover valuable products from TPO by distillation but also to gather key information for future optimization steps, as well as for bringing the process at industrial scales.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrolysis: Pyrolysis or thermal degradation (up to 800 °C) produces tyre-derived fuel known as tar pyrolysis oil (TPO) that has similar properties to diesel fuel. TPO can be used as heating, power generation, and automobile fuels, or in biorefineries [ 28 ]. The thermal degradation of tyres, however, requires a complex setup, high capital cost, skilled operators, and supplemental fuel to initiate and maintain the incineration process [ 29 ].…”
Section: Rubber—polyisoprenesmentioning
confidence: 99%
“…This waste made of natural and synthetic rubber, carbon black, textile material, steel, sulfur, and additives can be thermochemically converted (pyrolyzed), generating tire pyrolysis oils having a comparable calorific value to petroleum . Thermal degradation of waste tires leads to broad and complex chemical composition, dominated by hydrocarbons, classically requesting in-depth characterization. , Interestingly, also PAHs, from the cyclization and aromatization of the thermal degradation product butadiene, and amines as well as thiophenes, from additives and manufacturing accelerators, were found . Prospectively, studying the chemical composition of this alternative feedstock will be of high interest for evolved gas analysis soft photoionization mass spectrometry in the framework of a circular economy, particularly taking into account the vital field of co-pyrolysis together with other feedstocks, such polymers and biomass.…”
Section: Alternative Feedstock Energy Materialsmentioning
confidence: 99%
“…159,160 Interestingly, also PAHs, from the cyclization and aromatization of the thermal degradation product butadiene, and amines as well as thiophenes, from additives and manufacturing accelerators, were found. 161 Prospectively, studying the chemical composition of this alternative feedstock will be of high interest for evolved gas analysis soft photoionization mass spectrometry in the framework of a circular economy, particularly taking into account the vital field of co-pyrolysis together with other feedstocks, such polymers and biomass.…”
Section: ■ Liquid Fossil Petroleum and Distillatesmentioning
confidence: 99%